Sequevar Diversity and Virulence of Ralstonia solanacearum Phylotype I on Mayotte Island (Indian Ocean) - Chesneau, Thomas; Maignien, Géraldine; Boyer, Claudine; Chéron, Jean-Jacques; Roux-Cuvelier, Michel; Vanhuffel, Luc; Poussier, Stéphane; Prior, Philippe (Frontiers in Plant Science, 2018)
The genetic and phenotypic diversity of the Ralstonia solanacearum species complex, which causes bacterial wilt on Mayotte, was assessed in 140 strains sampled from Solanaceae collected from the main vegetable production areas of this island. Only phylotype I strains were identified in the five surveyed areas. The strains were distributed into the following 4 sequevars: I-31 (85.7%), I-18 (5.0%), I-15 (5.7%) and I-46 (3.6%). The central area of Mayotte was the most diverse region, harbouring 4 sequevars representing 47.1% of the collected strains. Pathogenicity Virulence tests were performed under field and controlled conditions on a set of ten tomato breeding line accessions and two commercial hybrid tomato cultivars. The strains belonging to sequevar I-31 showed the highest pathogenicity virulence on the tomatoes (pathotypes T-2 and T-3), whereas sequevars I-18, I-15 and I-46 were grouped into the weakly pathogenic T-1 pathotype. When the tomato accessions were challenged in the field and growth chambers, the highest level of resistance wereas observed from the genetically related accessions Hawaiiï 7996, R3034, TML46 and CLN1463. Thesese sources of resistanceaccessions were considered moderately to highly resistant to representative strains of the most pathogenic virulent and prevalent sequevar (I-31). Interestingly, the Platinum F1 cultivar, which was the most popular commercial line in Mayotte, was highly or moderately resistant to all strains. This study represents the first step in the rationalization of resistance deployment strategies against bacterial wilt-causing strains in Mayotte.